Reading With Mom : Reading Habits Among Rural Readers In Sarawak - Ambigapathy, Pandian; Damien, Mikeng; Erlinda, Mikal; Kundrata, Katelynn Dawn (AESS Publications, 2019)
The role of the mother in the literacy development of a child has been well studied, but only a few have linked this development with reading habits practiced amongst nonnative English-speaking mothers. The current study investigates the choices of English language reading materials for at home reading activities for the mother and child in addition to the motivation that influences this reading habit. Results from the 31 participants from a rural area of Sarawak have shown a significant pattern in favor of fiction genre materials compared to nonfiction reading materials for at home reading activities. This suggests that the variety of information from the fiction-based materials draws more interest and motivation for these mothers to read with their children. Other factors which determine the choices of materials are the proficiency levels of these nonnative English-speaking mothers and the age of the child involved. The findings are significant because this population is often overlooked and thus this study supplements the perspectives of nonnative English-speaking mothers toward literacy activities in the home.